KAJIAN SIFAT TERMODINAMIKA DALAM NANOSTRUKTUR SEMIKONDUKTOR - , Syamsurizal ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The calculations of energy spectrum for quantum dots (QD) with both spherical and cylindrical symmetries in the material of gallium arsenide (GaAs) have been done using a harmonic potential and ignoring Coulomb interaction. Furthermore calculation of the partition function is the basis for calculating thermodynamic quantities using Einstein models. The results indicate that there are different thermodynamic properties of systems between cylindrical and spherical QD where the cylindrical QD gives the more thermodynamic quantities than those of spherical QD systems. Generally the profile of thermodynamic quantities of nanostructure system show the same pattern with the bulk materials.